Digital heritage : progress in cultural heritage: documentation, preservation, and protection : 6th International Conference, EuroMed 2016, Nicosia, Cyprus, October 31-November 5, 2016, Proceedings /: progress in cultural heritage: documentation, preservation, and protection : 6th International Conference, EuroMed 2016, Nicosia, Cyprus, October 31-November 5, 2016, Proceedings. (2016) - Unknown
No abstract available